Real time bengali speech to text conversion using CMU sphinx - Kabir, Humayun; Ahmed, Ruhan; Nasib, Abdullah Umar (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.